Change in hepatocyte nuclear-cytoplasmic ratio at nontuberculosis mycobacteria infection against the background of immunomodulator action - E. A. Kosobokov; T. S. Dudoladova (Ветеринария сегодня)
The study was targeted at the examination of the effect of the specific immunomodulator KIM-M2 on the morphostructure of liver cells of guinea pigs infected with nontuberculosis mycobacteria. The research was carried out in 15 guinea pigs selected by gender at the Diagnostic Research and Biotechnology Laboratory of the Department of Veterinary Medicine of the Omsk Agrarian Scientific Center. All animals were kept in a specialized animal keeping facilities according to standard housing and feeding regime. The experimental animals were subdivided into three groups of five animals in each: group 1 – challenge group (Mycobacterium scrofulaceum), group 2 – experimental group (Mycobacterium scrofulaceum and KIM-M2), group 3 – pure control group (saline solution). On day 30 after the start of the experiment, the animals were removed from the experiment, liver biopsy samples were collected and histologic specimens were prepared according to the classical method. During the experiment, it was found that KIM-M2 had a regenerative effect on the liver tissue of the guinea pigs infected with nontuberculosis mycobacteria, which was associated with 1.5-fold increase in the number of mononuclear hepatocytes, 3-fold increase in binuclear cells and 4.3-fold decrease in anucleate hepatocytes thus indicating the manifestation of compensatory reactions in the organ and increase in the depth of regenerative processes. As for animals in group 1; 1.8and 1.3-fold increase in the area of the nucleus and cytoplasm as compared with the individuals in group 2, and 2.7and 2-fold increase as compared with the animals in the control group, respectively, indicated the launch of the accumulation mechanisms of the potential reparative reserves and increase in their depth in the liver tissues.